Shelf Life of Enzymatic Electrochemical Sensors. (2017) - Panjan, P.; Ohtonen, E.; Tervo, P.; Virtanen, V.; Sesay, A.M.
Abstract: Shelf life estimation of bio-sensing devices are important, especially when one wants to consider the commerciality of the system or device. Here we propose a mathematical model from a set of laboratory experiments based on accelerated aging due to elevated temperatures on glucose oxidase modified screen printed electrodes as a model electrochemical biosensor.